Simultaneous partial nitrification and 2-fluorophenol biodegradation with aerobic granular biomass: Reactor performance and microbial communities. (August 2017) - Ramos, Carlos; Amorim, Catarina L.; Mesquita, Daniela P.; Ferreira, Eugénio C.; Carrera, Julián; Castro, Paula M.L.
Graphical abstract: Highlights: Nitritation and biodegradation of 2-fluorophenol were achieved in granular reactor. Stable aerobic granules were maintained 135 days in a sequencing batch reactor. 2-Fluorophenol feeding decreased the species richness. The microbial community changed by treating 2-fluorophenol. Aerobic granular reactors are a promising technology for industrial wastewaters. Abstract: An aerobic granular bioreactor was operated for over 4 months, treating a synthetic wastewater with a high ammonium content (100 mg N L −1 ). The inoculum was collected from a bioreactor performing simultaneous partial nitrification and aromatic compounds biodegradation. From day-56 onwards, 2-fluorophenol (2-FP) (12.4 mg L −1 ) was added to the feeding wastewater and the system was bioaugmented with a 2-FP degrading bacteria ( Rhodococcus sp. FP1). By the end of operation, complete 2-FP biodegradation and partial nitrification were simultaneously achieved. Aerobic granules remained stable over time. During the 2-FP loading, a shift in the community structure occurred, coinciding with the improvement of 2-FP degradation. DGGE analysis did not allow to infer on the bioaugmented strain presence but pyrosequencing analysis detected Rhodococcus genus by the end of operation. Together with other potential phenolic-degraders within granules, these microorganisms were probably responsible for 2-FP degradation.